2015
DOI: 10.1007/s10336-015-1230-5
|View full text |Cite
|
Sign up to set email alerts
|

GPS tracking of Red Kites (Milvus milvus) reveals fledgling number is negatively correlated with home range size

Abstract: To date, reliable studies on the spatial area use and home range size of the Red Kite (Milvus milvus) during the breeding season are lacking. Between 2007 and 2014, 43 adult individuals were fitted with GPS transmitters in Germany. The home range sizes of 27 males, which successfully reared 47 broods, ranged between 4.8 and 507.1 km 2 based on the 95 % kernel utilization distribution. The median during the nestling and post-fledging dependent periods was 63.6 km 2 . The home ranges of 12 females, with a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 9 publications
5
45
2
Order By: Relevance
“…In our study habitat composition influenced nightjars’ home range size, and results of previous studies suggest that food availability determines nightjars’ foraging distance (Sierro et al , Sharps et al ). In cases of landscape heterogeneity (Camacho et al , Godet et al ) or where the distribution and availability of food resources fluctuates (Penteriani et al , Pfeiffer and Meyburg ), home range size can be affected. However, it is unclear how these factors influence nightjars’ foraging behaviour on a northwestern European scale.…”
Section: Discussionmentioning
confidence: 99%
“…In our study habitat composition influenced nightjars’ home range size, and results of previous studies suggest that food availability determines nightjars’ foraging distance (Sierro et al , Sharps et al ). In cases of landscape heterogeneity (Camacho et al , Godet et al ) or where the distribution and availability of food resources fluctuates (Penteriani et al , Pfeiffer and Meyburg ), home range size can be affected. However, it is unclear how these factors influence nightjars’ foraging behaviour on a northwestern European scale.…”
Section: Discussionmentioning
confidence: 99%
“…The concomitant reduction in the availability of favourable foraging habitat in the close vicinity of nesting sites thereby increases foraging distances and possibly reduces adult fitness and the time available for defence of nests. This in turn should result in a lower proportion of successful broods and a lower survival of nestlings (also see Pfeiffer & Meyburg 2015 for Milvus milvus). These findings are in line with the habitat heterogeneity hypothesis and support the findings of previous studies suggesting that as a consequence of increasing population density birds have been increasingly forced to breed in suboptimal habitats (Ferrer & Donazar 1996, Both 1998, Fernandez et al 1998, Kr€ uger & Lindstr€ om 2001, Carrete et al 2006, Kr€ uger et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, López-López et al (2016) found that the median value of home ranges of sixteen booted eagles, tagged by satellite as part of the 'Migra' project, was more extensive than those mentioned before for Murcia and Madrid, and showed no significant differences between sexes. In the same way, for red kites (Milvus milvus) the home ranges obtained by direct observation and VHF radio tracking tend to be smaller than those obtained using GPS satellite technology, because these methods do not allow data to be obtained from flights further away from the nest (Pfeiffer & Meyburg 2015). Home range sizes depend on many factors such as the availability of food, the quality and suitability of the habitat, intra-and inter-specific competition or how far away the food sources are from the nest (Newton 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Satellite tracking has been shown to be an effective and accurate tool for studying so far untreatable or insufficiently known aspects of the biology of birds, such as fidelity to territories, mortality, habitat use and the extent of their territories (see Meyburg et al 2006, Margalida et al 2008, Hernández-Pliego et al 2014, Pfeiffer & Meyburg 2015, among many others). In order to study its migration, satellite telemetry was first used with the booted eagle Aquila pennata in 2006, when two adult females were marked in the community of Madrid for which data during the breeding season of a female booted eagle (Aquila pennata) tagged by satellite in central Catalonia (Spain) were received from their autumn migration and wintering in Mauritania and Mali respectively (Diaz & Cebollada 2011).…”
Section: Introductionmentioning
confidence: 99%